2012
DOI: 10.2106/jbjs.k.00069
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications of Posterior Ankle and Hindfoot Arthroscopy

Abstract: Our experience demonstrated that posterior ankle and hindfoot arthroscopy can be performed with a low rate of major postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 42 publications
5
108
1
7
Order By: Relevance
“…Our technique described above also allows for safe placement of internal fixation by using established portals within anatomic safe locations 2 with a low rate of major complications. 3 This technique provides several advantages over standard open reduction internal fixation. The primary advantage is the limited soft tissue disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Our technique described above also allows for safe placement of internal fixation by using established portals within anatomic safe locations 2 with a low rate of major complications. 3 This technique provides several advantages over standard open reduction internal fixation. The primary advantage is the limited soft tissue disruption.…”
Section: Discussionmentioning
confidence: 99%
“…By not using the well-leg holder, the potential neurovascular injury from sustained pressure on the popliteal fossa is also eliminated. 3,4,7 Moreover, this method removes all reprocessed sterile equipment, thus cutting costs and the burden regarding the sterilization process and operating room staff. The external positioning arm is commonplace in operating rooms in which shoulder arthroscopy is performed; in most cases the burden of purchasing the equipment has already been met.…”
Section: Discussionmentioning
confidence: 99%
“…6 These techniques decreased the iatrogenic complication rate to 8% but required lengthy setup times and several pieces of sterilely processed equipment. 7 Thus we propose a 1-step simple ankle arthroscopy distraction technique that uses an external positioning arm to allow the surgeon to apply manual traction in multiple positions without the use of any reprocessed sterile equipment (Table 1).…”
mentioning
confidence: 99%
“…Dancers returned to sport faster with arthroscopic management as well at 6 to 8 weeks versus 8 to 24 weeks with open techniques. 54 The largest and most comprehensive study looking at complications after posterior arthroscopy was reported by Nickisch and colleagues 55 and demonstrated a complication rate of 8.5%. Open surgery complication rates have been reported between 10% and 24% (Fig.…”
Section: Clinical Outcomesmentioning
confidence: 99%